Pengaruh Penambahan Zat Aditif Fosroc Conplast R dan Fosroc SP 337 Terhadap Kuat Tekan Beton Dengan Variasi Kadar Air - Syafri Wardi; Aulia Kartika Sridewi; Arman A. (Media Ilmiah Teknik Sipil, 2021)
Fosroc Conplast R and Fosroc SP 337 are additives for the concrete mixture which are used to delay the setting time of the concrete mixture, thus, it can extend the time for the concreting work. Previous studies have verified that the addition of Fosroc SP 337 and/or Fosroc Complast R additives increases the compressive strength of concrete, but no previous studies have investigated the effect of adding these additives on the compressive strength of concrete with variations in water-cement ratio. Therefore, this research is conducted to investigate the effect of adding Fosroc Conplast R and Fosroc SP 337 additives on the compressive strength of concrete with variations in water-cement ratio, by conducting the test on properties of the materials for designing the concrete mixture proportion, then the compressive strength test is conducted and the compressive strength of concrete is compared with the design compressive strength based on SNI 03-2834-2000. The compressive strength test was conducted at the concrete age of 7 and 28. Concrete with the addition of 1% Fosroc Conplast R and 1% Fosroc SP 337 additives, produces a higher compressive strength than the design strength of normal concrete without additives, thus, this additive is applicable to extend the time for the concreting work in the construction field